Diversifying reading activities in english 8 textbook: action research study in a secondary school In Ha noi = Đa dạng hóa các hoạt động đọc trong sách giáo khoa lớp 8: Một nghiên cứu hành động tại một trường cấp 2 ở Hà Nội - Hoàng, Lan Chi (2020)
The research was conducted in a secondary school with grade 8th English as a Foreign Language (EFL) students with a view to investigating the impacts of diversifying reading activities on the teaching and learning of reading skill, and students’ attitudes toward its application. The thesis followed the action research framework. Participants of the research were 50 EFL students in grade 8, studying in the same English class at a secondary school in Hanoi. Data were collected by questionnaires, filled by the students, and the teacher’s observation. Analysis of the data showed that the diversification of reading activities was useful in that it made the learning of reading skill more effective, motivating and accessible to students. Also, there was a positive change of students’ attitudes towards learning reading skill. Therefore, it is concluded that diversification of reading activities was beneficial and should be employed EFL classes.